PROSPEK AGROINDUSTRI PALA DI WILAYAH PESISIR (SUATU STUDI DALAM RANGKA PEMBERDAYAAN MASYARAKAT DI DESA SEITH KECAMATAN LEIHITU KABUPATEN MALUKU TENGAH) - Wenno Noviar F. (PIRAMIDA, 2015)
Nutmeg (Myristica Fragrans Houtt) is known as herb plants that have high economic value and multifunction.Every part of the plant can be utilized in various industries. Seeds, mace and nutmeg oil are export commodities andare used in the food and beverage industry. Moreover, the oil derived from the seeds, mace and leaves are widelyused for industrial pharmaceuticals, perfumes and cosmetics. Thus, if nutmeg is managed wisely, it can increasethe income of people who working on it. Seith village is one of the areas in the coastal region particularly in LeihituDistrict Central Maluku district which has the largest land with the highest cultivation of nutmeg (Myristica frangans)which is 326.5 ha compared to other villages in the region, and has some RTU nutmeg oil that was not well developedand be bogged down. This will greatly affect the agricultural sector’s contribution to the economy of the region ..The Declining of diversified products such as nutmeg oil due to a lack of raw materials supply as a result of lowpurchase price offered by cooperative to society and high price of as it must be purchased from Ambon; whereas theabsence of the processed nutmeg flesh was caused by low perspective towards the prospects of processed nutmegflesh and nescience of nutmeg farmers on processing the nutmeg flesh into other products.